Effect Of Various Grinding Mechanisms During Particle Production - Mazlee, Muhammad Ihsan Firdaus (Universiti Sains Malaysia, 2018)
There are several types of grinding machines that were used in industry such as ball mill, planetary mill, jet mill, stirred mill and ring mill. These machines share the same purpose that is to reduce the size of a sample. Moreover, in a grinding process, mechanisms of grinding like impact and abrasion took place. These mechanisms can be manipulated as it varies with operating parameter. Two types of samples were used in this experiment that is limestone and granite. 20kg of each sample were crushed with jaw crusher and cone crusher. Then, the samples undergoes several grinding machines with different type of operating parameter. The grinding machine used were ball mill, planetary mill and ring mill. The results obtained show that ball mill and planetary mill at high rotational speed, the impact mechanism will be dominant, whilst at low rotational speed, the abrasion mechanism is more dominant. For different size of grinding media for ball mill, 45mm steel ball shows that it can reduce coarser material but 27mm steel ball shows that smaller size material are grind efficiently. For different number of ball or BPR, shows that 10:1 BPR produce impact mechanisms while 3:1 BPR gives abrasion mechanism. For ring mill, it produces very fine product in a short time due to high intensity of impact and abrasion. Moreover, for different type of machine, ball mill produces much wider size distribution if compared to planetary and ring mill. For different type of sample, granite are hard to grind compared to limestone due to higher strength.